Influence of Composition of SiCN as Interfacial Layer on Plasma Activated Direct Bonding. (19th June 2019) - Inoue, Fumihiro; Peng, Lan; Iacovo, Serena; Phommahaxay, Alain; Verdonck, Patrick; Meersschaut, Johan; Dara, Praveen; Sleeckx, Erik; Miller, Andy; Beyer, Gerald; Beyne, Eric
Abstract : Surface activated bonding is more and more attractive as a key technology to realize higher performance CMOS devices independent of scaling. The major challenge of dielectric bonding is to decrease the process temperature in order to be compatible with CMOS processing. In the past, we demonstrated low temperature bonding using SiCN as interfacial dielectric layer, where we have obtained a bond energy above 2.2 J/m 2 with a post bond annealing process of 250°C. In this work, the composition of SiCN was varied aiming at the identification of the key elements taking part in the bonding mechanism. The film density, roughness, CMP outcome, water contact angle and impact of plasma activation have been investigated on three different compositions of SiCN. Bond energy above 2.5 J/m 2 is obtained for the carbon rich SiCN film.